RETRACTED: SRI36160 is a specific inhibitor of Wnt/β-catenin signaling in human pancreatic and colorectal cancer cells. (28th March 2017) - Li, Yonghe; Oliver, Patsy G.; Lu, Wenyan; Pathak, Vibha; Sridharan, Sivaram; Augelli-Szafran, Corinne E.; Buchsbaum, Donald J.; Suto, Mark J.
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Authors. Following publication of this paper in Cancer Letters, the authors identified that SRI36160 and its analogs are potential inhibitors of the firefly luciferase. In particular, SRI36160 greatly inhibits the activity of firefly luciferase in the ATP-dependent luciferase ATPlite assay (Perkin Elmer) for cell proliferation studies, although SRI36160 has little or no effect on the activity of firefly luciferase in the CellTiter-Glo assay (Promega) for cell proliferation studies. This suggests that the activity of firefly luciferase can be significantly inhibited by SRI36160 in certain assay systems. As the cell proliferation data described in Fig. 5 in this paper was obtained from the ATP-dependent luciferase ATPlite assay, the data and cell proliferation IC50 values are incorrect. In addition, as the Super8XTOPFlash luciferase Wnt reporter assay is also based on firefly luciferase activity, the data and Wnt activity IC50 values described in Fig. 1A, 1B, 2A, 3A & 3B are likely to be inaccurate. All other data in this paper are correct. However in order to ensure the highest standard of data accuracy all the authors of this paper have requested that it be retracted from Cancer Letters.